ANALISIS EFEKTIVITAS PENERAPAN MOBILE BANKING LIVIN DALAM MENARIK MINAT NASABAH (STUDI PADA BANK MANDIRI KCP SOLO SLAMET RIYADI) - Triyanto, Triyanto; Ratnaningrum, Ratnaningrum; Susilowati, Heni; Sulistyowati, Pemilia; Henny, Henny; Sati, Dian Laras (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
This study aims to determine the effect of performance expectancy, effort expectancy, social influence, facilitating conditions and security simultaneously on customer interest (Study at Bank Mandiri KCP Solo Slamet Riyadi). This type of quantitative research with a survey method approach, sampling techniques using purposive sampling, and calculated using the Slovin formula, so that a research sample of 222 customers was obtained. Data collection techniques using questionnaires, and data analysis using multiple linear regression. Performance expectancy, effort expectancy, social influence, facilitating conditions and security have a positive and significant effect both partially and simultaneously on customer interest. The results show that effort expectations are the most important aspect in supporting customer interest, so the ease and convenience of operating e-banking must be improved.